Environmental factors and risk of multiple sclerosis: Findings from meta-analyses and Mendelian randomization studies - Belbasis, Lazaros; Bellou, Vanesa; Evangelou, Evangelos; Tzoulaki, Ioanna (Multiple sclerosis, 2020)
Multiple sclerosis (MS) is a chronic demyelinating disease that is associated with permanent disability and low quality of life. Development of MS is attributed to a combination of genetic and environmental factors. Genome-wide association studies revealed more than 200 variants that are associated with risk of MS. An umbrella review showed that smoking, history of infectious mononucleosis, and anti-Epstein-Barr virus nuclear antigen (anti-EBNA) immunoglobulin G (IgG) seropositivity are credible risk factors of MS. In the present narrative review, we updated our published umbrella review, showing that body mass index in childhood and adolescence and anti-viral capsid antigen (anti-VCA) IgG seropositivity are additional credible risk factors of MS. In addition, we discuss the findings from Mendelian randomization studies, which present evidence for a potential causal role of serum vitamin D and adulthood body mass index on risk of MS. Finally, we discuss the potential limitations of meta-analyses, umbrella reviews, and Mendelian randomization studies in the search for risk factors of MS.